Sexual desire in a sample of married Egyptian women with polycystic ovarian syndrome. Issue 3 (September 2015) - Elkhiat, Yasser; Zedan, Ashraf; Mostafa, Mona; Elhalwagi, Ahmed; Alhosini, Sara
Abstract : Purpose: The aim of this study was to evaluate sexual desire in a sample of married Egyptian women with polycystic ovarian syndrome (PCOS). Patients and methods: This study was carried out on 85 married Egyptian women with PCOS and 63 normal married women (the control group) recruited from the gynecology and obstetrics clinic in Kasr El-Aini Hospital, Cairo University. Every case was subjected to full medical history, full sexual history, general and local examinations, and investigated for serum levels of luteinizing hormone, follicle-stimulating hormone, and testosterone. Pelvic ultrasound was performed and BMI was calculated. Each case was interviewed using a structured interview to answer the translated Arabic version of Female Sexual Desire Questionnaire (FSDQ) developed by Goldhammer and McCabe (2011). Results: Total FSDQ score showed significantly higher level in the control group compared with the PCOS group ( P <0.001). Except for the solitary desire score, which was higher in the PCOS group than in the control group ( P =0.02), all other domains of the FSDQ – namely, dyadic desire, resistance, positive relationship, concern, and sexual self-image – exhibited statistically significantly higher level in the control group (( P <0.001) than in the PCOS group. Among PCOS women, there was significantly higher FSDQ score among women without androgenic alopecia ( P =0.02) and with normal testosterone level ( P =0.04). Conclusion: PCOS had a negative impact on female sexual desire. Although PCOS patients suffered from hyperandrogenism, they experienced decreased sexual desire, lacked the responsive sexual desire, and were less satisfied with the relationship with their partner. They were less confident with their bodies and experienced distress in relation to their sexual desire level. The presence of higher level of testosterone or androgenic alopecia in PCOS women is associated with reduced sexual desire.